Analysis of Bioconcentration Factors of Blood Mussels (Anadara granosa) on Pulau Pasaran, Bandar Lampung - Meliana Geovini Sinurat; Tugiyono Tugiyono; Elly Lestari Rustiati; Gregorius Nugroho Susanto (Ann Publisher, 2026)
Background. Pulau Pasaran, Teluk Betung Barat, Bandar Lampung, has an important role in supporting the fisheries sector and has been designated as a minapolitan area. This region is vulnerable to heavy metal contamination due to anthropogenic activities such as domestic and industrial waste. Aims. This study aims to analyze the concentration of heavy metal copper (Cu) in seawater and blood cockles in the waters of Pulau Pasaran, Bandar Lampung, and to calculate the bioconcentration factor (BCF) as an indicator of the potential accumulation of these metals in marine organisms. Methods. Samples were collected using a purposive sampling method during November–December 2025 at three locations: the Belau River estuary area, residential areas, and mangrove areas. Seawater and blood cockle samples were analyzed using the Inductively Coupled Plasma–Optical Emission Spectroscopy (ICP-OES) method in accordance with SNI 6989-82:2018 standards. Result. The results showed that Cu concentrations in blood cockles ranged from 0.936 to 1.303 mg/kg, which are still below the quality standard threshold based on the Decree of the Director General of BPOM No. 03725/B/SK/VII/89. Meanwhile, Cu concentrations in seawater ranged from <0.003 mg/L and remained below the threshold established by Government Regulation of the Republic of Indonesia No. 22 of 2021. The BCF values were classified as moderate accumulation (209.46–422.56), falling within the range of 100–1000 L/kg, with the highest value observed in the mangrove area. Conclusion. The results indicate that Pulau Pasaran waters are moderately contaminated with heavy metals, and that blood cockles can still be used as bioindicator organisms for monitoring heavy metal accumulation in aquatic environments.